Care during labor and birth: mothers’ perception - Francisca Alanny Araújo Rocha; Iellen Dantas Campos Verdes Rodrigues; Isabelle Rodrigues de Carvalho; Fernanda Maria Carvalho Fontenele; Rosalice Araújo de Sousa; Antônio Rodrigues Ferreira Júnior (Rev Rene)
Objective: to describe the care provided to women during labor and delivery in their perception. Methods: study with qualitative approach, developed in a hospital in the northern region of the state of Ceará, with 14 mothers. The analysis explored the content in the light of good care practices during labor and birth, recommended by the National Humanization Policy. Results: the mothers’ speeches revealed the need to make the environment more welcoming and the care more humanized during childbirth, contemplating listening to their problems and their concerns; satisfaction with the use of non-pharmacological methods used for pain relief and with the care given during labor. Conclusion: it was revealed how much human involvement and the search for a qualified assistance to mothers in maternity wards have contributed significantly to the quality of these actions.